Comparison of Axis II psychosocial assessment methods of RDC/TMD and DC/TMD as part of DC/TMD‐FIN phase II validation studies in tertiary care Finnish TMD pain patients. (27th September 2021) - Hietaharju, Maria; Kivimäki, Ida; Heikkilä, Henriikka; Näpänkangas, Ritva; Teerijoki‐Oksa, Tuija; Tanner, Johanna; Kemppainen, Pentti; Tolvanen, Mimmi; Suvinen, Tuija; Sipilä, Kirsi
Abstract: Background: The Research Diagnostic Criteria for Temporomandibular Disorders (RDC/TMD) and Diagnostic Criteria for TMD (DC/TMD) include Axis II instruments for psychosocial assessment. Objectives: The aims were to compare the Finnish versions of Axis II psychosocial assessment methods of the RDC/TMD and DC/TMD and to study their internal reliability. Methods: The sample comprised 197 tertiary care referral TMD pain patients. The associations between RDC/TMD [Graded Chronic Pain Scale (GCPS) 1.0, Symptom Check List 90‐revised (SCL‐90R)] and DC/TMD (GCPS 2.0, Patient Health Questionnaire‐9 (PHQ‐9), PHQ‐15) assessment instruments were evaluated using Spearman correlation coefficients, Wilcoxon Signed Rank s, chi‐squared test and gamma statistics. The internal reliability and internal inter‐item consistency of SCL‐90‐R, PHQ‐9, PHQ‐15 and Generalized Anxiety Disorder‐7 (GAD‐7) were evaluated using Cronbach's alpha coefficient values. Results: The DC/TMD and RDC/TMD Axis II psychosocial instruments correlated strongly ( p < .001). GCPS 1.0 and GCPS 2.0 grades were similarly distributed based on both criteria. The RDC/TMD psychological instruments had a higher tendency to subclassify patients with more severe symptoms of depression and non‐specific physical symptoms compared to DC/TMD. The internal reliability and internal inter‐item consistency were high for the psychological assessment instruments. Conclusion: The Finnish versions of the RDC/TMD and DC/TMD Axis II psychosocial instruments correlated strongly among tertiary care TMD pain patients. Furthermore, the Axis II psychological assessment instruments indicated high validity and internal inter‐item consistency and are applicable in Finnish TMD pain patients as part of other comprehensive specialist level assessments, but further psychometric and cut‐off evaluations are still needed.